The monovalent cation "leak" transport in human erythrocytes: an electroneutral exchange process. - Richter, S (1997)
The mechanism of the "ground permeability" of the human erythrocyte membrane for K+ and Na+ was investigated with respect to a possible involvement of a previously unidentified specific transport pathway, because earlier studies showed that it cannot be explained on the basis of simple electrodiffusion. In particular, we analyzed and described the increase in the (ouabain+bumetanide+EGTA)-insensitive unidirectional K+ and Na+ influxes as well as effluxes (defined as "leak" fluxes) observed in erythrocytes suspended in low-ionic-strength media. Using a carrier-type model and taking into account the influence of the ionic strength on the outer surface potential according to the Gouy-Chapman theory (i.e., the ion concentration near the membrane surface), we are able to describe the altered "leak" fluxes as an electroneutral process. In addition, we can show indirectly that this electroneutral flux is due to an exchange of monovalent cations with protons. This pathway is different from the amiloride-sensitive Na+/H+ exchanger present in the human red blood cell membrane and can be characterized as a K+(Na+)/H+ exchanger.